THE DEVELOPMENT OF AGROINDUSTRY AND TRANSPORTATIONAL NETWORK IN THE CENTRAL JAVA DURING DUTCH COLONIZATION - Hartatik, Endah Sri (Paramita: Historical Studies Journal, 2014)
The Java Land has been developed into a big plantation area, especially a sugar cane and coffee plantation. Those plantation was carried out since the seventeenth century by VOC , and then it is developed rapidly in nineteenth century, especially in the cultivation system period. The development of plantation company needs supporting vehicles and facilities. As a result of this, there are a development of land transportation, especially a train since the middle of the nineteenth century and the water transportation includes a big ships which enliven some harbours in Java, such as Semarang, Jakarta, Cirebon and Surabaya. Keywords: agroindustry, transportation network, Dutch colonization Â Tanah Jawa pernah berkembang menjadi wilayah perkebunan yang besar, terutama perkebunan tebu dan kopi. Usaha perkebunan itu mulai dilakukan sejak abad ke-17 oleh VOC, dan berkembang pesat pada abad ke-19, terutama sejak masa Tanam Paksa. Perkembangan perusahaan perkebunan memerlukan sarana pendukung transportasi. Akibatnya berkembanglah transportasi darat, terutama kereta api sejak pertengahan abad ke -19 dan transportasi laut berupa kapal-kapal besar yang meramaikan sejumlah pelabuhan laut di Jawa, seperti Semarang, Jakarta, Cirebon, dan Surabaya. Kata kunci:Â  agroindustry, jaringan transportasi, kolonial Belanda Â